Madame Sosostris and the festival for the brokenhearted - Okri, Ben (Other Press, 2025)
"In this modern fable with the impish magic of A Midsummer Night's Dream, a masked ball makes two upper-class British couples see each other in a new light. A wise, enchanting novel about love, power, and our many selves-past and future, public and private-from the Booker Prize-winning author. There are organizations for people who grieve, for alcoholics and other kinds of addicts. But if you've been devastated by the love of your life walking out on you, where the hell do you go? On the 20th anniversary of the day her first husband left her, Viv decides to host an unconventional party for those burned by love. She successfully ropes in her reluctant second husband, Alan, and their friends Beatrice and Stephen, and when she meets the famed fortuneteller Madame Sosostris-last seen in T. S. Eliot's The Waste Land, and rumored to be the secret to success of 5 prime ministers-she believes she's found the perfect act to headline her masquerade. In a sacred wood in the south of France, the partygoers disguise themselves and wait eagerly for the great clairvoyant, who might be able to mend their broken pasts and brighten their futures. But the night soon goes awry, in a comically revealing way that causes our couples to question their relationships and the direction of their lives"--